Apnea hypopnea indices categorized by REM/NREM sleep and sleep positions in 100 children with adenotonsillectomy for obstructive sleep apnea disease. (April 2019) - Nagao, Asuka; Komori, Masahiro; Kajiyama, Taihei; Shimasaki, Mutsumi; Hirakawa, Daigo; Kobayashi, Taisuke; Hyodo, Masamitsu
Abstract: Objectives: In pediatric obstructive sleep apnea (OSA), the relationship between rapid eye movement sleep and upper airway collapse, and between sleep position and airway dimensions are well known. However, the interrelations between these factors and the obstructive apnea hypopnea index (O-AHI) have not been thoroughly investigated. Methods: A retrospective study including 100 children who underwent adenotonsillectomy between March 2010 and July 2017. Total O-AHI was divided into four subcategories by sleep stage and position. Results: Preoperatively 14 of 47 mild cases of OSA (1 ≤ total O-AHI) and 17 of 18 moderate (5 ≤ total O-AHI) had time showing severe apnea (10 ≤ subcategorized O-AHI). Twenty-two of 24 severe cases (10 ≤ total O-AHI) exhibited very severe apnea (30 ≤ subcategorized O-AHI). All 11 very severe cases (30 ≤ total O-AHI) experienced more than 50 apnea events per hour in at least one of the O-AHI subcategories. After surgery, 23 of 70 cases classified as completely resolved (total O-AHI < 1) still had mild apnea in the O-AHI subcategories, and six of 13 cases who continued to experience apnea events had moderate-to-severe apnea. Seventeen cases worsened in the O-AHI subcategories, and total O-AHI deteriorated in two cases of the 17. The amount of REM sleep and use of the supine position increased significantly postoperatively in the quartile groups with the lowest baseline values ( p  < 0.0001). Conclusions: When an unexpected AHI value is encountered, the O-AHI subcategories may be informative regarding the indications for surgery and evaluating the efficacy thereof.